2015
DOI: 10.1111/jfpp.12583
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mineral Composition of Some Wild Edible Plants Growing in the Eastern Anatolia Region Grasslands of Turkey and Consumed as Vegetable

Abstract: This study was conducted to determine the mineral contents and some nutritional properties of four wild edible plants (Bellevalia forniculata, Beta corolliflora, Caltha polypetala and Primula auriculata) growing in the grasslands of Eastern Anatolia Region, Turkey and are consumed as vegetable. This is the first scientific report on the nutritional composition of these species. The moisture content, pH, ash and total nitrogen content of the plants ranged from 79.73 to 86.10%, 4.85 to 5.61, 7.33 to 17.12% and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 29 publications
5
20
0
4
Order By: Relevance
“…With regard to the iron (Fe) contents, the mean values ranges were observed to range from 25.0 to 1732.2 mg kg -1 (Turan et al 2003, Renna et al 2015, Tunctürk and Özgökçe 2015. In the previous studies, mean contents of Cu vary from 1.8 -46.3 mg kg -1 for edible plants (Turan et al 2003, Indrayan et al 2005, and also zinc levels reported for edible plants were 6.78 -68.65 mg kg -1 (Renna et al 2015, Tunctürk and Özgökçe 2015, Kibar and Temel 2016. The aforementioned elements are considered that they are useful for human health and run in a number of physiological functions in living organisms.…”
Section: Resultsmentioning
confidence: 89%
“…With regard to the iron (Fe) contents, the mean values ranges were observed to range from 25.0 to 1732.2 mg kg -1 (Turan et al 2003, Renna et al 2015, Tunctürk and Özgökçe 2015. In the previous studies, mean contents of Cu vary from 1.8 -46.3 mg kg -1 for edible plants (Turan et al 2003, Indrayan et al 2005, and also zinc levels reported for edible plants were 6.78 -68.65 mg kg -1 (Renna et al 2015, Tunctürk and Özgökçe 2015, Kibar and Temel 2016. The aforementioned elements are considered that they are useful for human health and run in a number of physiological functions in living organisms.…”
Section: Resultsmentioning
confidence: 89%
“…The K, PO 4 , and SO 4 are the most common ions present in the galls with a concentration of 5,671.21 mg/kg, 1,037.42 mg/kg, and 665.71 mg/kg, respectively. Similarly, K content was found to be highest in the wild edible plants ( Kibar & Temel, 2015 ) , fruit and leaves ( Kumari, Parida, Rangani, & Panda, 2017; Yildirim, Şan, Yildirim, Polat, & Ercişli, 2015 ) , and vegetables ( Oladejo et al., 2019 ) . These results showed superior potential of QIG in terms of K content indicating that QIG could be evaluated as a rich K source.…”
Section: Resultsmentioning
confidence: 98%
“…According to our previous researches, there were abundant functional compounds in health vegetables [8]. Besides, health vegetables were important sources of micro-minerals and vitamins [9] [10]. Therefore, these vegetables had enormous potential for health related researches and industries such as drug discover, food nutritional engineering and pharmaceutical industry.…”
Section: Introductionmentioning
confidence: 99%